Pengukuran Kinerja Bursa Kerja Khusus Sekolah Menengah Kejuruan dalam Meningkatkan Keterserapan Lulusan di Dunia Kerja - Nur Fitriana; Sri Wibawani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to describe and analyze the level of achievement of the performance of the Bursa Kerja Khusus (BKK) of Vocational High School in Sidoarjo Regency to improving the absorption of graduates in the working field. The problem focused on BKK's performance has not been effective in carrying out its duties as a work placement service organization and career guidance to students and vocational school graduates  in the same manner as the absorption of graduates in the working field, namely The World Business and Industry is still below 75% and vocational school graduates as the highest contributor of open unemployment in Sidoarjo Regency in August 2018-August 2020. To approach the problem used performance assessment theory from Dwiyanto (2018) there are; productivity, service quality, responsiveness, responsibility, and accountability. This research uses descriptive quantitative research methods. The results showed that the performance of BKK SMK Sidoarjo Regency obtained a percentage of 42.5% and the results of each sub-variable performance; (1) productivity dimension obtained 42.5% (2) dimension of service quality obtained 55% (3) dimension of responsiveness obtained 42.5%, (4) dimension responsibilities obtained 50%, and (5) dimension accountability obtained 37.5%.